the Effectiveness of Zakat Applications in Improving Transparency and Accountability - Magomed Tazhdinov; Nur Fitri Hidayanti (Universitas Muhammadiyah Mataram, 2025)
Abstract: The development of digital technology has opened up new opportunities in zakat management, making research on the effectiveness of digital-based zakat applications important to ensure that zakat management is increasingly transparent, accountable, and in accordance with sharia principles. This study aims to analyze the effectiveness of digital-based zakat applications in improving the transparency and accountability of zakat management through a Systematic Literature Review (SLR) approach. Literature sources were obtained from reputable databases, namely Scopus, DOAJ, and Google Scholar, covering publications from 2015 to 2025. A systematic review process was conducted to identify, evaluate, and synthesize relevant findings from previous studies. The results showed that digital zakat applications were effective in strengthening the transparency and accountability of zakat institutions, particularly through increased information disclosure, financial reporting accuracy, zakat distribution monitoring, and increased community participation. These findings confirm that the digitization of zakat plays a strategic role in building the trust of muzaki, strengthening the accountability of zakat management organizations, and encouraging the optimization of zakat governance in accordance with sharia principles. Thus, this study not only contributes conceptually to the development of academic literature on the digitization of zakat, but also offers practical recommendations for zakat institutions and regulators in designing more transparent, accountable, and sustainable digital-based zakat management strategies.Abstrak: Perkembangan teknologi digital telah membuka peluang baru dalam pengelolaan zakat, sehingga penelitian mengenai efektivitas aplikasi zakat berbasis digital penting dilakukan untuk memastikan tata kelola zakat semakin transparan, akuntabel, dan sesuai prinsip syariah. Penelitian ini bertujuan untuk menganalisis efektivitas aplikasi zakat berbasis digital dalam meningkatkan transparansi dan akuntabilitas pengelolaan zakat melalui pendekatan Systematic Literature Review (SLR). Sumber literatur diperoleh dari basis data bereputasi, yaitu Scopus, DOAJ, dan Google Scholar, dengan cakupan publikasi pada rentang tahun 2015–2025. Proses telaah sistematis dilakukan untuk mengidentifikasi, mengevaluasi, dan mensintesis temuan-temuan penelitian terdahulu yang relevan. Hasil penelitian menunjukkan bahwa aplikasi zakat digital terbukti efektif dalam memperkuat transparansi dan akuntabilitas lembaga zakat, terutama melalui peningkatan keterbukaan informasi, akurasi pelaporan keuangan, monitoring distribusi zakat, serta peningkatan partisipasi masyarakat. Temuan ini menegaskan bahwa digitalisasi zakat berperan strategis dalam membangun kepercayaan muzaki, memperkuat akuntabilitas organisasi pengelola zakat, dan mendorong optimalisasi tata kelola zakat sesuai prinsip syariah. Dengan demikian, penelitian ini tidak hanya memberikan kontribusi konseptual bagi pengembangan literatur akademik mengenai digitalisasi zakat, tetapi juga menawarkan rekomendasi praktis bagi lembaga zakat dan regulator dalam merancang strategi pengelolaan zakat berbasis digital yang lebih transparan, akuntabel, dan berkelanjutan.